Rumah Rumah Kita: Model Pemberdayaan Perempuan Tani Secara Terpadu Menuju Pencapaian SDG’s - Fatchiya, Anna; Wijianto, Arip; Prasetyo, Kunandar; Sulistiawati, Asri (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Peasant women play an essential role in achieving the SDG's. Women's self-capacity must be improved through non-formal education, namely rural development extensions. Community service activities in the Returning Home Lecturers Program were conducted at the Putri Langgeng Peasant Women's Group in Godog Village, Polokarto District, Sukoharjo Regency, Central Java. The aim is to increase women's knowledge, awareness, and skills in terms of increasing digital literacy, namely being able to use cellphones wisely and utilizing the Rumah Sawit application as IPB's innovative work, early detection of stunting symptoms, utilizing yard land to increase family income, preventing and dealing with violence against women and children. The impact of community service helps achieve SDG's goals, namely goal #1, no poverty; #3, good health and well-being; and #4, quality education. The impact of this community service is an increase in household income, with vegetable yields worth an average of IDR 100.000 per month, and catfish harvests from tarpaulin ponds between IDR 300.000‒400.000 per growing season. Other impacts of various vegetables and Calina papaya have been introduced to the village community and outside the village. In the health sector, stunting mats have been used by four Godog Village posyandus as a tool for early detection of stunting.